VOCABULARY AND GRAMMAR DIFFERENCES IN ENGLISH-SPEAKING COUNTRIES - Qo‘chqarova Zulfizar; Ro‘ziyeva Nilufarxon Adhamjon qizi (Лучшие интеллектуальные исследования, 2023)
Abstract: This article discusses the key differences in speaking English across countries, including accents, vocabulary, grammar, syntax, and cultural influences. The paper emphasizes how these differences contribute to the richness and diversity of the English language, while also noting that, despite these differences, English- speaking countries are generally able to understand each other due to the widespread use of American English in media and popular culture. Overall, the abstract emphasizes the evolving and adaptable nature of English in various parts of the world.